2020
DOI: 10.1007/s00264-020-04892-4
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition as predictor of poor outcome after total hip arthroplasty

Abstract: Introduction The aim of this study was to assess the prevalence of protein energy malnutrition (PEM) and correlation with poor post-operative outcome in the elderly undergoing primary total hip arthroplasty (THA). Hypothesis Patients with PEM would have inferior post-operative outcome after THA. Materials and method We retrospectively evaluated the nutritional status of 220 hospitalized patients undergoing THA, 65 years and older. PEM was assessed using serum albumin and total lymphocyte count (TLC). Studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…Whereas albumin had the highest specificity and a positive predictive value compared to all other markers such as total lymphocyte count and transferrin. Other studies have also confirmed the association of hypoalbuminemia with complications of arthroplasty from surgical site infection to pneumonia, cardiovascular pathology, and urinary tract infection [9,21,22,23]. Like the above reports, our findings showed low albumin and hemoglobin as the most prevalent (>50%) abnormal laboratory values.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Whereas albumin had the highest specificity and a positive predictive value compared to all other markers such as total lymphocyte count and transferrin. Other studies have also confirmed the association of hypoalbuminemia with complications of arthroplasty from surgical site infection to pneumonia, cardiovascular pathology, and urinary tract infection [9,21,22,23]. Like the above reports, our findings showed low albumin and hemoglobin as the most prevalent (>50%) abnormal laboratory values.…”
Section: Discussionsupporting
confidence: 90%
“…The average preoperative prevalence of PEM in patients undergoing arthroplasty depending on the heterogeneity of the cohort has been widely reported at 8.5%, 12.3%, 53% and 80% [13,15,15,20,21]. At the time of hospital admission, most of our patients (>70%) had laboratory signs of PEM.…”
Section: Discussionmentioning
confidence: 68%
“…It has been suggested that preoperative nutritional assessment in patients with CP sequela helps in improving the clinical condition of the patients (7). Malnutrition has been seen as a contributing factor to the development of postoperative complications due to suppressed immune system, delayed wound healing, and worsening of gastroesophageal reflux (8,9). The simplest method that can be used to evaluate the immune system status is to calculate the absolute lymphocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that compared to older people with good nutritional status, those with undernutrition or high undernutrition risk show low immunity, poor resistance, decreased quality of life, prolonged hospital stay, increased hospital costs, poor treatment effect, poor prognosis, and high incidence of complications (6)(7)(8)(9). Numerous studies have demonstrated the association of undernutrition with a high incidence of and mortality due to fractures and various diseases in older individuals (10)(11)(12)(13)(14)(15). Therefore, considering the increasing proportion of older individuals in China, the "Healthy China 2030 Program Outline" and improvements in the nutritional status and health of all citizens in China need to be implemented.…”
Section: Introductionmentioning
confidence: 96%